(untitled) (CAHIERS MAGELLANES-NS, 2024)
This article examines the transformative impact of digital commerce on the global corporate landscape, with a particular emphasis on the Indian market. The COVID-19 epidemic has expedited the growth of electronic commerce, resulting in significant changes in consumer behavior and retail trends. India's Open Network for Digital Commerce (ONDC) initiative seeks to democratize digital commerce, promote inclusivity, and stimulate innovation while tackling digital monopolies. This study investigates the opportunities and challenges in the digital commerce ecosystem by critically examining ONDC and its consequences for small enterprises, local vendors, and consumers. Key issues include decentralization, interoperability, governance, etc.